2020
DOI: 10.1177/1071100720969618
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Achilles Tendon Lengthening and Gastrocnemius Recession on Radiographic Tibiotalar Motion Following Total Ankle Replacement

Abstract: Background: Surgeons frequently add an Achilles tendon lengthening or gastrocnemius recession to increase dorsiflexion following total ankle replacement. Previous studies have looked at the effects of these procedures on total tibiopedal motion. However, tibiopedal motion includes motion of the midfoot and hindfoot as well as the ankle replacement. The current study examined the effects of Achilles tendon lengthening and gastrocnemius recession on radiographic tibiotalar motion at the level of the prosthesis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…The study had the unexpected results of a statistically significant loss of 11.7 degrees of PF in the TAL group; however, preoperative ROM radiographs were only available in 27 of the 54 patients for comparison (TAL n=10, GR n=3, control n=14). 14 A few limitations of this study were the lack of preoperative ROM parameters (only 50% of patients) and clinical rather than radiographic ROM measurements. Our study results similarly confirmed a loss of PF in the TAL cohort; however, the same phenomena were true of the GR cohort.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The study had the unexpected results of a statistically significant loss of 11.7 degrees of PF in the TAL group; however, preoperative ROM radiographs were only available in 27 of the 54 patients for comparison (TAL n=10, GR n=3, control n=14). 14 A few limitations of this study were the lack of preoperative ROM parameters (only 50% of patients) and clinical rather than radiographic ROM measurements. Our study results similarly confirmed a loss of PF in the TAL cohort; however, the same phenomena were true of the GR cohort.…”
Section: Discussionmentioning
confidence: 93%
“…However, as previously mentioned, tibiopedal motion includes motion of the midfoot and hindfoot as well as the ankle replacement. Jeng et al 14 examined the effects of TAL and GR on radiographic tibiotalar motion at the level of the prosthesis only. Fifty-four patients with an average of 25 months’ follow-up after TAR were divided into patients who underwent TAL, GR, or no lengthening procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Foot & Ankle International 44 (3) mostly. Of note, the greater PF loss for the GR group than the TAL group could not be explained by these speculations, and it warrants further study.…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%
“…5 Additionally, under this assumption, the more PF loss in the GR group indicated more loss of push-off strength, which is not consistent with the authors’ previous study. 2 Besides, Jeng et al 3 conducted a similar study and obtained somewhat different results, with TAL exhibiting greater PF loss conversely. We reviewed the literature 1,2,3,5 and our institutional experience of TAR to attempt to explain this issue: (1) postoperative immobilization after heel cord lengthening tends to be more dorsiflexion to avoid recurrence of equinus deformity; (2) the majority of physiotherapy rehabilitation exercises focus on dorsiflexion, and it is easier for patients to passively force dorsiflexion by themselves than plantarflexion; and (3) the plantarflexion weakness leads to a chronic anterior ankle contracture over time.…”
mentioning
confidence: 99%